Experimental Substantiation for Applying Cryopreserved Preparations of Embryofetoplacental Complex in Thyroid Gland Pathology Correction. Report I. Effect of fetal thymus preparations on rabbit thyroid gland functional activity - Malova, N. G.; Yurchenko, T. M.; Bozhko, T. S.; Komarova, I. V.; Strona, D. V.; Solonets, Yu. M.; Chujkova, V. I. (Problems of Cryobiology and Cryomedicine, 2007)
The xenotransplantation effect of human fetal thymus cryopreserved biopreparation on rabbit’s thyroid gland functional activity with a suppressed thyroid function (experimental mercazolil hypothyrosis) has been studied. A normalizing effect of the performed therapy on experimental animals’ thyroid system has been noted. Stimulating effect of the preparation was proved to be a two-phase: approaching to the maximum by the 2nd month after engraftment and a gradual leveling by the 4th one. A repeated engraftment of thymus tissue stimulates a thyroid function in animals, that indicates to the capability of suppressed thyroid gland for a multiple recovery of activity after fetal thymus tissue transplantation.